The doctrine of creation ; part 2 - Barth, Karl, 1886-1968; Torrance, Thomas Forsyth, 1913-; Bromiley, Geoffrey William (Edinburgh, Scotland T and T Clark, 1960)
Includes indexes.
Original German ed. : Die Kirchliche Dogmatik, II : Die Lehre von der Schopfung, 2
Keywords: Creation -- man